SHOULDER FLEXIBILITY IN COLOR GUARD PLAYER FOLLOWING POSTERIOR SHOULDER STRETCHING AND MUSCLE ENERGY TECHNIQUE - Tria Fitri Nurjani; Hilmi Zadah Faidlullah (Proceedings of the International Conference on Applied Science and Health, 2017)
Background: Color guard players often exhibited loss of glenohumeral joint range of motion (ROM) in internal rotation which has been associated with shoulder pathology. Current stretching protocols aimed at improving flexibility of the posterior shoulder have resulted in different outcomes and previous studies have not been discussed color guard players for the subject. Aims: This study was to determine the differences effects between non assisted posterior shoulder stretching (NAPSS) and muscle energy technique (MET) to increase internal rotation ROM of glenohumeral joint of the color guard marching band. Methods: This study is experimental pre test and post test two group design, the subjects are 18 color guard players. The subjects were divided into 2 groups that 9 subjects in group I treated NAPSS and 9 subjects in group II treated MET. The treatment was given for 5 times per week in 2 weeks. This study used goniometer for measuring internal rotation ROM. Saphiro Wilk test for the normality test. Paired sample T-test to determine increasing of internal rotation ROM for group I and group II. Independent sample T-test to determine the differences effect between group I and group II. Result: The result of paired sample T-test is p=0.001 (p< 0.05) in group I and p=0.001 (p< 0.05) in group II which exhibited that there is an effect the treatment of both posterior shoulder stretching and muscle energy technique to increase internal rotation ROM. The result of Independent sample T-test is p=0.084 (p >0.05) indicated that there is no different effect between posterior shoulder stretching and muscle energy technique. Conclusion: NAPSS and MET were capable of significantly increasing internal rotation ROM of glenohumeral joint and no different effects between the methods. Both methods can be used as stretching program before marching band exercise.